The Role of Vitamin D Deficiency in Pathogenesis of PCOS: A Case-Control Study Among Females in Mosul City (Iraqi Journal of Medical Sciences, 2024)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine condition primarily affecting women of reproductive age. The prevalence of PCOS is 3 to 10%. According to the pathogenesis of PCOS; obesity, hyperandrogenemia, insulin resistance (IR), hormonal imbalances and metabolic dysregulation are patterns of PCOS. Vitamin D deficiency may be associated with PCOS and it has been shown that low vitamin D levels may worsen PCOS symptoms.Objective: To prove the role of vitamin D deficiency in pathogenesis of PCOS. Methods: A case control study with a sample size of (80) women. The females included in this study were single or married but not pregnant. They were divided in to 2 groups: 40 females having PCOS and 40 females without PCOS. Parameters measured were total serum testosterone, serum prolactin level and vitamin D level by i-chroma, also body mass index (BMI) (kg/m2) and waist-hip ratio (WHR).Results: In PCOS group, (97.5%) of patients had low vitamin D levels, which is significantly higher than those of the control group who only (65%) of them had low vitamin D level. Also, PCOS group had significantly higher serum prolactin and serum testosterone than control group. The percentage of PCOS patients with irregular menstrual cycle was 80%, and with hirsutism was 57%, while with acanthosis was 42%. Conclusion: There is a relationship between vitamin D status and a variety of PCOS symptoms, emphasizing the possible contribution of vitamin D deficiency to symptom severity. Keywords: Polycystic ovary syndrome, vitamin D, serum prolactin, serum total testosterone.Citation: Abow FH, Alsarraf ZH, Ali HJ. The role of vitamin D deficiency in Pathogenesis of PCOS: A case-control study among females in Mosul city. Iraqi JMS. 2024; 22(2): 239-251. doi: 10.22578/IJMS.22.2.8
Keywords: Polycystic ovary syndrome; vitamin D; serum prolactin; serum total testosterone